Analisis Sebaran Total Suspended Solid (TSS) dan Oksigen Terlarut (DO) Dengan Menggunakan Satelit Citra Landsat di Pulau Lusi Kabupaten Sidoarjo - Hubertus Bebeto Wagi; Siti Zainab (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the districts in East Java is Sidoarjo. One of the natural beauties of Sidoarjo Regency is the Porong River, which is a branch of the Brantas River. At the mouth of the Porong River there is a delta called Lusi Island. The aim of this research is to monitor the distribution of dissolved oxygen (DO) on the distribution of Total Suspended Solids (TSS) on the coast of Lusi Island, Sidoarjo Regency. The contribution of Civil Engineering in this research can provide important information in planning and developing maritime infrastructure, such as ports and docks, which can influence the sustainability of the economic and transportation sectors. Therefore, it is necessary to conduct research on the distribution of dissolved oxygen and the distribution of Total Suspended Solids by utilizing technology from Landsat 8 satellite data and monitoring the distribution pattern. This system uses a mathematical algorithm to get the best results. Later, field conditions will confirm the results of the analysis. The aim of this research is to evaluate the distribution of Total Suspended Solid and Dissolved Oxygen in the coastal area of ​​Lusi Island. The results of the analysis show that the field data values ​​taken in Bulau in May 2024 ranged between 80 mg/L and 146 mg/L for Total Suspended Solid, and 5.13 mg/L and 7.38 mg/L for dissolved oxygen. Meanwhile, the image data value for Total Suspended Solid is 10.68 mg/L – 165.13 mg/L and for dissolved oxygen the distribution is 4.69 mg/L – 6.94 mg/L. Both field data have a weak positive correlation value of 0.17266739.